Eradicating Helicobacter pylori infection lowers gastrin mediated acid secretion by two thirds in patients with duodenal ulcer. Issue 8 (August 1993) - el-Omar, E; Penman, I; Dorrian, C A; Ardill, J E; McColl, K E
Abstract : Helicobacter pylori (H pylori) raises serum gastrin but it is unclear whether this stimulates increased acid secretion. Gastrin mediated acid secretion and plasma gastrin after the intravenous infusion of gastrin releasing peptide was studied in nine H pylori negative and nine H pylori positive healthy volunteers, and in 11 duodenal ulcer patients. Nine of the last group were re-examined one month after eradication of H pylori. The median acid output (mmol/h) to gastrin releasing peptide (40 pmol/kg/h) in the H pylori positive healthy volunteers was 15.1 (range 3.3-38.3), which was three times that of the H pylori negative healthy volunteers (median = 5.5, range 1.0-9.0) (p < 0.02). The median acid output in the duodenal ulcer patients with H pylori was 37 (range 8.5-57), which was > six times that of the H pylori negative healthy volunteers. Eradication of H pylori in the duodenal ulcer patients lowered their acid secretion by a median of 66% (range 30%-80%) (p < 0.01) and to values equivalent to the H pylori positive healthy volunteers. The pepsin output in response to gastrin releasing peptide followed the same pattern as the acid output. The median plasma gastrin concentrations during gastrin releasing peptide were similar in the H pylori positive duodenal ulcer patients (150 ng/l, range 95-400) and H pylori positive healthy volunteers (129 ng/l, range 23-420) and both were appreciably higher than H pylori negative healthy volunteers (60 ng/l, range 28-135) (p < 0.005 for each). Eradication of H pylori lowered the plasma gastrin in the duodenal ulcer patients to values equivalent to the H pylori negative healthy volunteers. These findings show a threefold increase in acid secretion in H pylori positive healthy volunteers that is explained by H pylori induced hypergastrinaemia and a sixfold increase in acid secretion in the duodenal ulcer patients that is explained by the combination of H pylori induced hypergastrinaemia and an exaggerated acid response to stimulation by gastrin. Eradicating H pylori lowers gastrin mediated acid secretion by 66% in duodenal ulcer patients as a result of the resolution of the hypergastrinaemia. Increased gastrin mediated acid secretion seems to be the key factor in the pathophysiology of duodenal ulceration and explains the role of H pylori infection in the disorder.